2020
DOI: 10.1371/journal.pone.0235809
|View full text |Cite
|
Sign up to set email alerts
|

Investigating SOFA, delta-SOFA and MPM-III for mortality prediction among critically ill patients at a private tertiary hospital ICU in Kenya: A retrospective cohort study

Abstract: Background Outcomes in well-resourced, intensive care units (ICUs) in Kenya are thought to be comparable to those in high-income countries (HICs) but risk-adjusted mortality data is unavailable. We undertook an evaluation of the Aga Khan University Hospital, Nairobi ICU to analyze patient clinical-demographic characteristics, compare the performance of Sequential Organ Failure Assessment (SOFA), delta-SOFA at 48 hours and Mortality Prediction Model-III (MPM-III) mortality prediction systems, and identify facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
(40 reference statements)
2
11
1
Order By: Relevance
“…These results were not the same as the study's findings by Lukoko et al (9) , which showed that most of the studied patients were males (61.4%), with a median age of 53 years. This study showed that diabetes and hypertension were the predominant chronic illnesses in the studied population.…”
Section: Discussioncontrasting
confidence: 80%
“…These results were not the same as the study's findings by Lukoko et al (9) , which showed that most of the studied patients were males (61.4%), with a median age of 53 years. This study showed that diabetes and hypertension were the predominant chronic illnesses in the studied population.…”
Section: Discussioncontrasting
confidence: 80%
“…MPM 0 -III has been externally validated in various ICUs in North America ( Higgins et al, 2007 ; Kuzniewicz et al, 2008 ; Higgins et al, 2009 ) and has shown to have good discrimination which was similar to our study finding. However, a study done at Aga Khan University Hospital, Nairobi, Kenya ( Lukoko et al, 2020 ) and two public ICUs in Rwanda ( Riviello et al, 2016 ) showed MPM 0 -III to have fair discrimination amongst their cohort. This observed difference in discrimination may be due to the effect of differences in proportion of case mixes between the study settings.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies mentioned that were conducted in Sub-Saharan Africa have produced contrasting results. The MPM 0 -III was well calibrated amongst the critical ill patients admitted to the ICU of the Aga Khan University Hospital, Nairobi ( Lukoko et al, 2020 ) but showed poor calibration amongst all adult patients admitted to Rwanda’s two public ICUs ( Riviello et al, 2016 ). These findings highlight the similar treatment protocols and interventions between two sister hospitals located in different geographical regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 This same group subsequently demonstrated that even the presence of a well-resourced ICU in an LMIC is not enough to guarantee good patient outcomes in the absence of protocolized care. 15 Protocolized care is urgently needed in low-resource environments to improve critical care outcomes.…”
Section: What Can We Do To Improve the Quality Of Critical Care In Re...mentioning
confidence: 99%